Kasuistik Evaluasi Pembelajaran Bahasa Arab (Siklus Refleksi Gibbs Dalam Penilaian Dan Pengukuran) - Azimah, Hanifa; Ridlo, Ubaid; Raswan, Raswan (CV. Green Publisher Indonesia, 2025)
This paper aims to describe the application of the Gibbs reflection cycle in measurement and assessment. This research is a descriptive qualitative research. The data was collected through interviews and analyzed with the Miles, Huberman and Saldana models. The results of this study show that the Gibbs reflection cycle can be used in measurement and assessment with the same stages, namely description, feelings, evaluation, analysis, conclusion/synthesis, and action plan.